2011
DOI: 10.1038/mt.2010.233
|View full text |Cite
|
Sign up to set email alerts
|

Properties of PEI-based Polyplex Nanoparticles That Correlate With Their Transfection Efficacy

Abstract: We have evaluated the key properties of the polyethylenimine (PEI)-polyethylene glycol (PEG)-TAT peptide polyplex nanoparticles including their behavior in cells and compared them with the transfection efficacy (TE) using 11 different cell lines. We found statistically significant positive correlation between TE and the share of 50-75 nm fraction in the whole mixture of nanoparticles estimated with atomic force microscopy. Variations in PEG/PEI and N/P ratios (PEI nitrogen to DNA phosphate ratio) enabled us to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 30 publications
4
72
0
4
Order By: Relevance
“…While this makes direct comparisons between studies difficult, it also suggests that the screening of any PEI-PEG library requires an indepth study using a wide range of substitutions and N/P ratios. While many studies have noted the importance of these variables, the relevance of the two variables acting in concert has only been considered via a transfection surface recently: Ulasov et al [33] reported the transfection surfaces (PEG chains/PEI vs N/P vs %transfection) of numerous cell types, all having similar peaks, but with the elevation dependent on cell type. The present study investigated a broader range of substitutions and N/P ratios in comparison, using 0-37.2 PEG/PEI with a maximum N/P = $70, whereas Ulasov et al used 0-8 PEG/PEI with a maximum N/P = $40.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While this makes direct comparisons between studies difficult, it also suggests that the screening of any PEI-PEG library requires an indepth study using a wide range of substitutions and N/P ratios. While many studies have noted the importance of these variables, the relevance of the two variables acting in concert has only been considered via a transfection surface recently: Ulasov et al [33] reported the transfection surfaces (PEG chains/PEI vs N/P vs %transfection) of numerous cell types, all having similar peaks, but with the elevation dependent on cell type. The present study investigated a broader range of substitutions and N/P ratios in comparison, using 0-37.2 PEG/PEI with a maximum N/P = $70, whereas Ulasov et al used 0-8 PEG/PEI with a maximum N/P = $40.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies suggest that siRNA delivery is less inhibited by PEI PEGylation than plasmid delivery [25,28], and lower stability of PEGylated complexes was attributed to greater cargo release intracellularly. By extension, it is possible that higher cytosolic unpacking may be the same reason for a high degree of PEGylation decreasing plasmid transfection; premature unpacking of polyplexes in the cytosol decreases the likelihood of the plasmid bypassing the nuclear envelope, owing to its larger size and negative charge [33]. The question remains then, how does a low degree of PEG substitution increase the transfection efficiency of PEI, compared with unmodified PEI?…”
Section: Transfection Properties Of Pei-peg Polyplexesmentioning
confidence: 92%
“…However, toxicity remains one of the challenges of this vector. There are many targets and assays that can be used to give better insight to different aspects of toxicity (Ulasov, 2011;Fischer et al, 2003;), while little is known about genotoxicity and intracellular ROS generation effects of PEI.…”
Section: Discussionmentioning
confidence: 99%
“…Cationic polymers and liposomes are the most studied nonviral vectors, with cationic polymers reported with significant differences because of their unique characteristics and potential to generate nanoparticles with DNA for gene delivery (Nakayama et al, 2005;Kafil and Omidi, 2011). Polyethylenimine (PEI) is one of the best-known cationic polymers, which has been widely used for nonviral transfection in vitro and in vivo (Ulasov et al, 2011). PEI is a cationic synthetic polymer available in linear and branched forms, and in a vast range of molecular weights, from <1000 Da up to 1.6 × 10 6 Da (Godbey and Mikos, 2001;Neu et al, 2005;Oskuee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…10.1021/acs.macromol.5b01824 Macromolecules XXXX, XXX, XXX−XXX D the quantity of free (unbound) PLKC20 was ∼82% of the initial concentration (18% are complexed with DNA).…”
mentioning
confidence: 99%